Online Versus Classroom Teaching: Impact on Teacher and Student Relationship Quality and Quality of Life - Vagos, Paula; Carvalhais, Lénia (Frontiers in Psychology, 2022)
The student-teacher relationship (STR) has been consistently associated to positive and generalized outcomes, though its quality seems to be questioned in online teaching, which in turn has had a negative impact on students and teachers’ wellbeing during school closures forced by the COVID-19 pandemic. The current work compared students and teachers’ perceptions of STR quality and quality of life after online and after classroom teaching, and if STR quality relates with perceived wellbeing across those teaching modalities. Participants were 47 teachers (61.7% female, Mage = 47.85) and 56 students (48.2% female, Mage = 13.13), who self-reported on the quality of STR and quality of life twice: after three months of online teaching and after three months of classroom teaching. Quality of life remained stable across teaching modalities. Teachers perceived no differences in teacher-student quality across both moments; students perceived higher conflict after classroom teaching. Closeness in STR associated with increased wellbeing and the reverse was true for conflict, though diverse domains of quality of life were implicated across timings and across teachers and students. These findings concur to online teaching being an impersonal experience for students, where conflict is lower due to the absence of social stimuli; alternatively, teachers may be urged to use the STR as a resource to sustain better positive outcomes even when teaching online, both for them and for their students.